Pengaruh Hedonic Shopping Motives dan Promosi Penjualan Terhadap Impulse Buying Konsumen di Matahari Department Store Manado Town Square - Florensia Jovita Poluan; Johny R. E. Tampi; Danny D. S. Mukuan (Universitas Sam Ratulangi, 2019)
This study is to determine: partial influence of Hedonic Shopping Motives on Impulse Buying; Partial influence of Sales Promotion on Impulse Buying; simultaneous influence of Hedonic Shopping Motives and Sales Promotions on Impulse Buying. Type of Research is quantitative research. The sample that used in this research were 100 respondents who were consumers in Matahari Department Store Manado Town Square. The sampling technique using is probability sampling and the method that using is purposive sampling. Methods of data collection by questionnaire. Data analysis using is multiple linear regression. The results showed that: There is significant partial effect of Hedonic Shopping Motives on Impulse Buying. There is no partial effect of Sales Promotions on Impulse Buying. There is simultaneous effect between Hedonic Shopping Motives and Sales Promotions on Impulse Buying. Based on the result, it shows that Matahari Department Store Manado Town Square management can use the hedon motivation from their consumer to increase their sales. The company should increase their sales promotion to get consumer attention and to make compete ability in Indonesia retail business